Repellent active ingredients encapsulated in polymeric nanoparticles: potential alternative formulations to control arboviruses - Abrantes, Daniele Carvalho [UNESP]; Rogerio, Carolina Barbara [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; Germano-Costa, Tais; Vigato, Aryane Alves; Machado, Ian Pompermeyer; Sepulveda, Anderson Ferreira; Lima, Renata; de Araujo, Daniele Ribeiro; Fraceto, Leonardo Fernandes [UNESP] (Springer Nature, 2022)
Dengue, yellow fever, Chinkungunya, Zika virus, and West Nile fever have infected millions and killed a considerable number of humans since their emergence. These arboviruses are transmitted by mosquito bites and topical chemical repellents are the most commonly used method to protect against vector arthropod species. This study aimed to develop a new generation of repellent formulations to promote improved arboviruses transmission control. A repellent system based on polycaprolactone (PCL)-polymeric nanoparticles was developed for the dual encapsulation of IR3535 and geraniol and further incorporation into a thermosensitive hydrogel. The physicochemical and morphological parameters of the prepared formulations were evaluated by dynamic light scattering (DLS), nano tracking analysis (NTA), atomic force microscopy (AFM). In vitro release mechanisms and permeation performance were evaluated before and after nanoparticles incorporation into the hydrogels. FTIR analysis was performed to evaluate the effect of formulation epidermal contact. Potential cytotoxicity was evaluated using the MTT reduction test and disc diffusion methods. The nanoparticle formulations were stable over 120 days with encapsulation efficiency (EE) of 60% and 99% for IR3535 and geraniol, respectively. AFM analysis revealed a spherical nanoparticle morphology. After 24 h, 7 ± 0.1% and 83 ± 2% of the GRL and IR3535, respectively, were released while the same formulation incorporated in poloxamer 407 hydrogel released 11 ± 0.9% and 29 ± 3% of the loaded GRL and IR3535, respectively. GRL permeation from PCL nanoparticles and PCL nanoparticles in the hydrogel showed similar profiles, while IR3535 permeation was modulated by formulation compositions. Differences in IR3535 permeated amounts were higher for PCL nanoparticles in the hydrogels (36.9 ± 1.1 mg/cm2) compared to the IR3535-PCL nanoparticles (29.2 ± 1.5 mg/cm2). However, both active permeation concentrations were low at 24 h, indicating that the formulations (PCL nanoparticles and PCL in hydrogel) controlled the bioactive percutaneous absorption. Minor changes in the stratum corneum (SC) caused by interaction with the formulations may not represent a consumer safety risk. The cytotoxicity results presented herein indicate the carrier systems based on poly-epsilon caprolactone (PCL) exhibited a reduced toxic effect when compared to emulsions, opening perspectives for these systems to be used as a tool to prolong protection times with lower active repellent concentrations.
Keywords: Arboviruses; Geraniol; Insect repellent; IR3535; PCL nanoparticle